Stress, anxiety and depression: Its relationship with quality of life among flood victims / Johana Johari and Najib Ahmad Marzuki - Johari, Johana; Marzuki, Najib Ahmad (Universiti Teknologi MARA Cawangan Pahang, 2017)
Natural disasters such as floods often leave psychological impact on victims. This study addresses the relationship between stress, anxiety and depression among flood victims and its relationship with quality of life. A total of 294 flood victims in the district of Kubang Pasu, Kedah, Malaysia were chosen as samples for this study. The study utilized the Depression, Anxiety and Stress Scale (DASS) to measure stress, anxiety and depression while the World Health Organization Quality of Life (WHOQOL-BREFF) and the Impact of Events Scale-Revised (IESR) was utilized to measure quality of life. Results indicated that stress, anxiety and depression have significant negative association with quality of life. In addition, stress and anxiety were found to be significant predictors to quality of life. Effective and efficient social and infrastructural support from the government, relevant authorities and agencies as well as from non-governmental organizations (NGOs) are needed to further strengthen and enhance the overall quality of life of flood victims.